2019
DOI: 10.18174/515048
|View full text |Cite
|
Sign up to set email alerts
|

Methane production from insect, worm and mushroom waste streams and combinations

Abstract: In literature, the synergistic effect of several substrates on feedstocks for anaerobic digestion/methane production is described for several substrates. Champost from mushroom production, vermicompost from worm composting/vermiculture and BSF (black soldier fly) larvae frass from insect production were therefore tested for this report for their synergistic effect. It was found that insect frass had a very high biogas/methane production as a single substrate. Addition of the frass led to a concentration depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
1
7
2
2
Order By: Relevance
“…Table 4 shows biogas productions from several reference substrates. The biogas production values differ between the measurements of this report and Elissen et al (2019). The dry matter percentage of the insect frass varies between 63 and 83 %, where the non-hygienised is the highest.…”
Section: Other Parameterscontrasting
confidence: 77%
See 3 more Smart Citations
“…Table 4 shows biogas productions from several reference substrates. The biogas production values differ between the measurements of this report and Elissen et al (2019). The dry matter percentage of the insect frass varies between 63 and 83 %, where the non-hygienised is the highest.…”
Section: Other Parameterscontrasting
confidence: 77%
“…According to Bulak et al (2020) 379.0 nm³/ton DM for mealworm frass, 389.5 nm³/ton DM for cricket frass and 351.4 nm³/ton DM frass for Hermetia illucens larvea frass (black soldier fly). In previous research a possible synergistic effect on the biogas production was found using a combination of digestate and insect frass from Hermetia illucens larvae (Elissen et al, 2019). Xie et al(2017a) also found a synergistic effect on specific methane yield when mixing primary sludge with food waste.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In general, (average) biogas productions from the different substrates with or without fungal pretreatment did not differ to a large extent and were relatively low (35-73 nm3 biogas per ton product) except for that from insect frass (274 nm 3 biogas per ton product): It was high and similar to that found in a previous experiment(Elissen et al, 2019). When comparing the numbers to other data, | Report WPR-832…”
supporting
confidence: 62%